Transformational Leadership and Professional Ethics as a Strategy for Preventing Sexual Crimes in Secondary Education Institutions in Kayong Utara Regency - Zulkarnaen, Zulkarnaen; Hartoyo, Agung; Zakso, Amrazi (LPPM Institut Pendidikan Nusantara Global, 2025)
The increasing prevalence of sexual violence in secondary school environments reflects the fragility of student protection systems, particularly in geographically challenged regions such as Kayong Utara Regency. This study aims to explore the implementation of transformational leadership and professional teaching ethics in efforts to prevent sexual violence in schools. Employing a qualitative approach with a multi-site case study design, the research was conducted in three secondary schools and one provincial education office. Data were collected through in-depth interviews, participatory observation, and document analysis, and subsequently analyzed using data reduction, open coding, axial coding, and methodological triangulation, with validation through member checks and peer debriefing. The findings reveal that some schools have integrated protection values into their school visions and leadership cultures. However, weaknesses persist in the reporting systems and external collaborations. These findings underscore the necessity of strengthening value-based governance and implementing systemic training in transformational leadership. The study recommends the institutionalization of professional teaching ethics, the development of standard operating procedures for student protection, and the establishment of safe and collaborative reporting channels. In conclusion, leadership and ethics are not merely technical strategies but moral foundations of an education system that prioritizes the safety and dignity of students.